Diversity Assessment of Selected Coconut (Cocos nucifera L.) Accessions using Microsatellite Markers - Nurul Alya Fakhiratunnisa; Dafni Mawar Tarigan; Shahril Ab Razak; Khairun Hisam Nasir; Kumeran Govindasamy (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Coconut (Cocos nucifera L.) is a multipurpose plant that has a very high level of cultivar diversity Almost all parts of the coconut plant, (Cocos nucifera L.) can be utilized and provide benefits for human life, In the fruit, from the skin to the coconut water, each has different functions and uses. This study aimed to determine the genetic diversity of selected coconut varieties. A total of 12 microsatellite markers were used to assess genetic diversity, 293 coconut individuals consisting of 19 coconut varieties, A total of 63 alleles were detected with an average of 5.25 alleles per locus. Polymorphic information content, (PIC) ranged from 0.1518 (C22) to 0.6778 (C2) with an average of 0.3546 per locus. Pairwise genetic distances ranged from 0.0361 (Malayan Red Dwarf-Malayan Green Dwarf) to 0.6585 (Malayan Yellow Dwarf-Rotuman). This value indicates a high similarity between the varieties Malayan Red Dwarf and MGD. The neighbor dendogram shows that the tall varieties Laguna, Rotuman, Markham, and Kar Kar are clustered together. Meanwhile, all dwarf varieties (MRD, MGD, MYD, Nias, Catigan, and CRD) are clustered together with the dwarf x dwarf hybrids Careca and Careni. These results provide important insights for future breeding activities and conservation management programs